Pre- and post-natal development of skin characteristics in the one humped camel(Camelus dromedarius) - MARAI, I F M; KHALIL, A B A (The Indian Journal of Animal Sciences, 2014)
The skin of camel, as in other farm animals is formed of 2 mai n layers: the epiderms and the dermis. The hypodermis was clearly seen only in the mid-side position than In the other regions of the body. The epidermis began to appear as a single row of cells at 90 days, then both the epidermis and dermis were Cully developed at 147 days of foelal life at which time the epldermis was difterentrated into Its 4 strata (corneum granulosum, spinosum and basale or germinativum), and the derms was differentiated into papillary and reticular sub-layers. The plugs which would for han the han follicles began to appear at 147 days, while the hair fibres began to appear in its follicles at 268 days of foetal life. The tollicle, began clearly differentiated into primary and secondary follicles at 268 days of foetal life The han follicles Were arranged in groups and were clearly seen at 375 days of foetal life. Each group consisted of 3 primary-follicles (1 central and 2 laterals) and several secondary foillcies (On the ectal Side orthe primary follicles). The thickest secondary follicles (early secondary follicles) were situated near the primaries, whlie the more thin secondaries (late secondary follicles) Were far from the primries. The primary follicle was associated with a sebaceous gland, a sweat gland and an arrector pili muscle while each secondary follicle was associated only With a sebaceous gland. The sebaceous glands that Were attached to the primary follicles had large lobules, while those attached to the secondarnes were small. The several lobules of the sebaceous glands open into a common short cxcretory duct. The selnlceoLls glands began to appear at 229 days of foetal life. The apocrine sweat gland was formed of a glandular the tuous part and Its uppermost straight duct passed between or beside the sebaceous glands lobules, then enlarged into a sae betore it opened near the follicle opening at the skin surface. The glandular tortuous distal part was situated either at or lower than the level of the hair follicle bulb, and was formed of 1 layer of cubOidal epithelium. The swcat glands began to appear at 229 days of foetal hfe. The alrector pill muscle was formed of Smooth musclc fibres. It ran from the lower part of the follicle to the arca below the epldermS. The aroector pili muscles first appeared at 229 days of foetal life.